THE ASSEMBLAGE OF INTERRELIGIOUS DIALOGUE AND TOURISM - Taufiqurrohim Taufiqurrohim (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2022)
The touristic place provides discourses that are worth examining as to which how the management of the site, its internal contestation and development, as well as experiences of its visitors. Examining a heritage of the ancient Majapahit kingdom in Java, this article discusses the assemblage of tourism and religious sites and the extent the site serves as a reservoir for interreligious dialog in contemporary Indonesia. It tries to point out how interreligious dialogue is at work in this site and how surrounding communities participate and respond to the perseverance of the site. Finally, accentuating Swidler’s theory of dialogues, this paper looks at the practice of interreligious dialogue at a touristic site and how religious harmony is negotiated by Buddhist and Muslim through the site and the construction of “the other” by both religious communities.